Implementasi Model SECI dalam Perencanaan Pulang untuk Kesiapan Pasien Stroke dalam Pemulangan: Literatur Riview - Sy, Yunizabetri; Huda, Nurul; Bayhakki (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Discharge planning is a crucial element in nursing care, especially for patients recovering from severe medical conditions like ischemic stroke. Effective discharge planning influences patient outcomes, including recovery levels and quality of life. This literature review aims to explore studies on the implementation of the SECI model in discharge planning for ischemic stroke patients. Databases used include Google Scholar, PubMed, ScienceDirect, Semantic Scholar, ResearchGate, and BMC, with a systematic literature review method. Keywords used were